Teaching history with musicals - Edney, Kathryn 1972- (Lanham Rowman & Littlefield, 2017)
"Popular media has become a common means by which students understand both the present and the past. Consequently, more teachers are using various forms of popular culture as pedagogical tools in the history classroom. With their resurgent popularity--on both the large and small screens--musicals can be used to engage students as an entertaining source of historical understanding. In order to facilitate the use of musicals as learning tools, however, teachers of history need a dependable resource. Teaching History with Musicals is a guide for teaching U.S. and world history. In addition to covering key themes and concepts, this volume provides an era-by-era overview of significant issues and related films, a tutorial in using film in historical methodology, user guides for ten key musical films, and sample exercises and assignments for direct classroom use. Covering eras from American settlement to the present, this books draws on both classic and contemporary musical motion pictures, including 1776, Pocahontas, The Jazz Singer, Cabaret, Footloose, Hairspray, and Rent. This resource enables teachers to effectively use films to examine key social and cultural issues, concepts, and influences in their historical context. Teaching History with Musicals will be an invaluable asset to any teacher of history in middle- and secondary school settings, as well as at the undergraduate level." -- Publisher's description
Concepts. A short history of musical films -- Historical concepts -- Approaches. Teaching United States history with musical films -- Teaching Western Civilization with musical films -- Documents. Sample syllabus -- Musicals for the classroom -- Further readings
Includes bibliographical references and index
Keywords: Musicals; United States -- History -- Study and teaching